Clinical activity of CC‐90011, an oral, potent, and reversible LSD1 inhibitor, in advanced malignancies. Issue 17 (23rd June 2022) - Hollebecque, Antoine; Salvagni, Stefania; Plummer, Ruth; Niccoli, Patricia; Capdevila, Jaume; Curigliano, Giuseppe; Moreno, Victor; de Braud, Filippo; de Villambrosia, Sonia Gonzalez; Martin‐Romano, Patricia; Baudin, Eric; Arias, Marina; et al.
Abstract : Background: CC‐90011 is an oral, potent, selective, reversible inhibitor of lysine‐specific demethylase 1 (LSD1) that was well tolerated, with encouraging activity in patients who had advanced solid tumors or relapsed/refractory marginal zone lymphoma. The authors present long‐term safety and efficacy and novel pharmacodynamic and pharmacokinetic data from the first‐in‐human study of CC‐90011. Methods: CC‐90011‐ST‐001 (ClincalTrials.gov identifier NCT02875223; Eudract number 2015–005243‐13) is a phase 1, multicenter study in which patients received CC‐90011 once per week in 28‐day cycles. The objectives were to determine the safety, maximum tolerated dose, and/or recommended phase 2 dose (primary) and to evaluate preliminary efficacy and pharmacokinetics (secondary). Results: Sixty‐nine patients were enrolled, including 50 in the dose‐escalation arm and 19 in the dose‐expansion arm. Thrombocytopenia was the most common treatment‐related adverse event and was successfully managed with dose modifications. Clinical activity with prolonged, durable responses were observed, particularly in patients who had neuroendocrine neoplasms. In the dose‐escalation arm, one patient with relapsed/refractory marginal zone lymphoma achieved a complete response (ongoing in cycle 58). In the dose‐expansion arm, three patients with neuroendocrine neoplasms had stable disease after nine or more cycles, including one patient who was in cycle 46 of ongoing treatment. CC‐90011 decreased levels of secreted neuroendocrine peptides chromogranin A, progastrin‐releasing peptide, and RNA expression of the blood pharmacodynamic marker monocyte‐to‐macrophage differentiation–associated . Conclusions: The safety profile of CC‐90011 suggested that its reversible mechanism of action may provide an advantage over other irreversible LSD1 inhibitors. The favorable tolerability profile, clinical activity, durable responses, and once‐per‐week dosing support further exploration of CC‐90011 as monotherapy and in combination with other treatments for patients with advanced solid tumors and other malignancies. Abstract : This first‐in‐human study evaluated CC‐90011, a highly potent, selective, and reversible oral lysine‐specific demethylase 1 inhibitor, in patients with advanced solid tumors and relapsed/refractory lymphoma. The tolerability, clinical activity, and once‐weekly dosing support further exploration of CC‐90011 in patients with advanced malignancies.